TRENDS IN THE EVOLUTION OF REGIONAL FAUNAS OF REGULAR ARCHAEOCYATHIDS - Naimark E.B.; Rozanov A.Yu. (My University, 1997)
Archaeocyathid fauna renewals are traced in eleven regions by dividing new genera of every chron into three groups: (1) immigrant genera, or colonizers; (2) aboriginal genera; and (3) genera, whose generation areas raise doubts. It is shown that dominant genera of the second group are important for detecting secondary centers of origin, while most abundant genera of the first group point to biotic invasions in the regions. The taxa prevalence in the third group is related to transgressions. Endemic genera mark the progressing specialization of taxa, but not the isolation of a region. As a rule, they appear in the centers of origin, and at the moments of peak diversity. Also analyzed are the growth, diversification, and regressive evolutionary stages of regional faunas.